BIOSORBEN ARANG BUAH JABON PUTIH (Anthocephalus cadamba Miq.) UNTUK MENJERAP ION LOGAM MERKURI (II) DALAM AIR - T Abu Hanifah; Sofia Anita; Itnawita Itnawita; Ganis Fia Kartika; Romauli Romauli (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2024)
The aim of this study was to analyze the adsorption ability and optimum stirring speed of non-activated white jabon fruit carbon and activated carbon on the absorption of mercury (II) ions. White jabon carbon is made through a carbonization process at a temperature of 300ºC for 30 minutes, then activated with NaOH and characterization of activated carbon is also carried out according to SNI 06-3730-1995. The optimization of stirring speed was carried out by varying the stirring speed of 60, 80, 100 and 120 rpm. The results of the characterization of activated carbon of white jabon fruit in this study showed a moisture content of 1.98%, ash content of 3.11%, iodine adsorption capacity of 1160.5285 mg/g and methylene blue adsorption capacity of 25.1024 mg/g. The results of the adsorption test on activated carbon of white jabon fruit showed that the optimum stirring speed condition was 80 rpm with an adsorption efficiency of 99.78% and an adsorption capacity of 0.9641 mg/g. Based on the results of the SEM test, it was found that the activated carbon had more pores than unactivated.